ARTIFICIAL INTELLIGENCE TOOLS IN TEACHING SOCIAL AND HUMANITARIAN DISCIPLINES - Anna Kyrpa; Olena Stepanenko; Viktoriia Zinchenko; Tetiana Datsiuk; Iryna Karpan; Neonila Tilniak (Інформаційні технології і засоби навчання)
Due to the rapid development of information technologies, the use of digital solutions for educational purposes is becoming increasingly relevant and promising. This encourages the evaluation and development of new methods that provide a personalized approach to teaching and learning, including integration of artificial intelligence (AI) tools that can revolutionize education. However, the question of teachers’ qualifications regarding the use of AI tools in their pedagogical activities, especially in social and humanitarian disciplines, remains unexplored. Therefore, the research goal is to investigate the level of competence of teachers of social and humanitarian disciplines when using AI tools in educational activities which involves educating users about the capabilities, limitations and proper use of these tools, understanding how to benefit from AI and how to avoid misuse.